2014
DOI: 10.3390/ijerph111212247
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Behaviour and Social and Health Factors in University Students from 26 Low, Middle and High Income Countries

Abstract: Poor oral health is still a major burden for populations throughout the world, particularly in developing countries. The aim of this study was investigate oral health behaviour (tooth brushing and dental attendance) and associated factors in low, middle and high income countries. Using anonymous questionnaires, data were collected from 19,560 undergraduate university students (mean age 20.8, SD = 2.8) from 27 universities in 26 countries across Asia, Africa and the Americas. Results indicate that 67.2% of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
82
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 44 publications
14
82
3
1
Order By: Relevance
“…Almost 27.8% of students reported brushing teeth after breakfast, this finding is anticipated with past researches that have shown 28% of adults used to brush their teeth at breakfast time so they could feel fresh at the beginning of the day [23]. In, addition, majority of students (98.1%) used toothbrush to brush their tongue, which is similar to past studies reporting (81.8%) of the students brushed their tongues by using tooth brush in the developing countries [22].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Almost 27.8% of students reported brushing teeth after breakfast, this finding is anticipated with past researches that have shown 28% of adults used to brush their teeth at breakfast time so they could feel fresh at the beginning of the day [23]. In, addition, majority of students (98.1%) used toothbrush to brush their tongue, which is similar to past studies reporting (81.8%) of the students brushed their tongues by using tooth brush in the developing countries [22].…”
Section: Discussionsupporting
confidence: 79%
“…This study indicates 62.9% of university students brushed their teeth before going to sleep, in contrast studies carried out in Nigeria and developing countries revealed 71.9% and 62.7% of undergraduates brushed their teeth twice a day [21,22]. Almost 27.8% of students reported brushing teeth after breakfast, this finding is anticipated with past researches that have shown 28% of adults used to brush their teeth at breakfast time so they could feel fresh at the beginning of the day [23].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the creation of a variable that represents all the elements considered as characterizing oral selfcare by the literature 7,8,10,12,17 is what makes this study so very distinct. As observed in the methodological description, the grouping of factors shows a high explanatory capacity, and the variable created can be used in other studies and in health planning involving more concrete strategies for self-care.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of oral health, the recognition and analysis of the process of acquiring individual autonomy is under construction, and studies predominantly show an association between oral self-care and isolated factors. 7,8,9,10,11 The literature points out that appropriate oral health depends on maintaining certain practices, including periodic dental visits, 12,13,14,15 tooth brushing frequency, 7,10,12,16,17 toothbrush replacement frequency, 17,18 dental flossing, and use of auxiliary techniques, 7,12,17,19 and that all these factors together represent oral selfcare. However, the studies usually evaluate oral selfcare in a segmented manner, relating it specifically to dental flossing, toothbrushing or regular visits to the dentist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation